THU0569 Pharmacokinetics and Pharmacodynamics of Canakinumab in Patients with Autoinflammatory Periodic Fever Syndromes (Colchicine Resistant FMF, HIDS/MKD and TRAPS). (15th July 2016) - De Benedetti, F.; Anton, J.; Gattorno, M.; Lachmann, H.; Kone-Paut, I.; Ozen, S.; Frenkel, J.; Simon, A.; Zeft, A.; Ben-Chetrit, E.; Hoffman, H.; Joubert, Y.; et al.
Abstract : Background: Periodic fever syndromes are a group of rare autoinflammatory conditions that includes, among others, cryopyrin-associated periodic syndromes (CAPS), familial Mediterranean fever (FMF), hyper-IgD syndrome/mevalonate kinase deficiency (HIDS/MKD) and TNF receptor-associated periodic syndrome (TRAPS). The pharmacokinetics (PK) of canakinumab (CAN) and total interleukin (IL)-1β kinetics have been well characterised in CAPS patients (pts). 1 Here we present the PK and pharmacodynamics (PD) of CAN in colchicine resistant/intolerant (crFMF), HIDS/MKD and TRAPS pts. Objectives: To evaluate the PK and PD of CAN (solution for injection-liquid in vial [LIVI]) from the phase III study in crFMF, HIDS/MKD and TRAPS pts at Week 16. Methods: The study (NCT02059291 ) comprised of 3 disease cohorts (crFMF, HIDS/MKD and TRAPS). Each cohort followed the same study design across 4 epochs (screening epoch [up to 12 weeks], randomised treatment epoch [16 weeks], randomised withdrawal epoch [24 weeks] and open-label treatment epoch [72 weeks]). Pts (age, ≥2 years) with crFMF, HIDS/MKD or TRAPS who had a flare during Epoch 1 were randomised (1:1) in Epoch 2 to receive subcutaneous (sc) CAN 150 mg (or 2 mg/kg for pts weighing ≤40 kg) every 4 weeks (q4w) or placebo. Blinded uptitration (up to 300 mg) was allowed for pts not resolving the index flare by day15. Samples for CAN concentrations and total IL-1β were collected at baseline (Day 1), and trough samples at weeks 2, 4, 8, 12 and 16. Results: In crFMF, HIDS/MKD and TRAPS pts, the serum clearance and steady-state volume of distribution of CAN varied according to body weight and were estimated to be 0.14±0.04 L/day and 4.96±1.35 L, respectively. The estimated half-life of CAN was 25.6±6.4 days. CAN minimal concentration at Week 16 following 150 mg sc q4w dosing was estimated to be 15.3±6.6 μg/mL. The estimated steady state area under the serum concentration-time curve from time zero to the end of the dosing interval tau (AUCtau ) was 648±202 μg.day/mL. Similar results were obtained in 3 diseases. CAN binding to circulating IL-1β was demonstrated by increase in total IL-1β following CAN dosing in all 3 diseases. In pts requiring up titration to 300 mg, levels of total IL-1β were higher suggesting higher production of IL-1β. Conclusions: This was first study to evaluate the PK characteristics of canakinumab given in the LIVI form. The results observed in crFMF, HIDS/MKD and TRAPS patients were similar to those observed in other indications (CAPS and SJIA) using the lyophilisate form. These data suggested that new formulation did not affect PK/PD of the drug and similarly to CAPS, patients with higher levels of IL-1β may require canakinumab up-titration to have an optimal disease control. References: Chakraborty A, et al. Clin Pharmacokinet. 2012;51:e1–18. Disclosure of Interest: F. De Benedetti Grant/research support from: Pfizer, Abbvie, Roche, Novartis, Novimmune, BMS, J. Anton Grant/research support from: Novartis, Pfizer, Abbvie, Roche, SOBI, Consultant for: Novartis, M. Gattorno Grant/research support from: Novartis, SOBI, Consultant for: Novartis, SOBI, Speakers bureau: Novartis, SOBI, H. Lachmann Consultant for: Novartis, SOBI, Takeda, GSK, Speakers bureau: Novartis, SOBI, I. Kone-Paut Grant/research support from: SOBI, Roche, Novartis, Consultant for: Novartis, SOBI, Pfizer, Abbvie, Chugai, S. Ozen Consultant for: Novartis, Speakers bureau: SOBI, J. Frenkel Grant/research support from: Novartis, SOBI, A. Simon Grant/research support from: CSL Behring, Novartis, Xoma/Servier, A. Zeft: None declared, E. Ben-Chetrit Consultant for: Novartis, H. Hoffman Grant/research support from: BMS, Consultant for: Novartis, SOBI, Regeneron, Speakers bureau: Novartis, Y. Joubert Employee of: Novartis, K. Lheritier Shareholder of: Novartis, Employee of: Novartis, A. Speziale Employee of: Novartis, G. Junge Employee of: Novartis, X. Xu Employee of: Novartis